Relationship between physical characteristics and undulation in the breaststroke - Colman, V.; Daly, D.; Desmet, S.; Persyn, U. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
In order to quantify undulation in breaststroke, five undulation factors were constructed from body positions during the stroke cycle: uphill in leg spreading, dome-shaped at the surface, S-shaped under the surface, and uphill hydroplaning in the two recovery phases. When international swimmers were placed in four groups, according to a total undulation index, one continuum from flat to extremely undulating was found in women. For men, two distinct groups were observed: the majority very flat and the others extremely undulating. Vhen the mean percentile scores of women and men for each separate undulation factor were presented in curves, the women showed higher scores in the S-shaped and the uphill, hydroplaning body position. Most of the individual curves of undulation factors were flat. The dome-shaped part of the undulation was related to good ankle supination combined with outward hip rotation for women. Apparently, the S-shaped and the striking uphill parts of the undulation in women can be explained by more flexibility in lumbar cambering, even when the hips were flexed. In men, a flat position was related to hip inward rotation and ankle outward rotation and flexion.